The Effect of Chatgpt on Vocational Students’ Writing and Plagiarism Awareness - I Gede Kardiyasa; Made Hery Santosa; I Putu Indra Kusuma (Jurnal Ilmiah Global Education, 2026)
Generative artificial intelligence (AI) such as ChatGPT is increasingly integrated into English as a Foreign Language (EFL) writing instruction. However, empirical evidence in vocational high school contexts remains limited, particularly concerning its impact on academic integrity. This quasi-experimental study examined the effects of ChatGPT-assisted writing instruction on students’ writing performance and plagiarism awareness. Sixty-eight tenth-grade students from a vocational high school in Bali were assigned to an experimental group (ChatGPT-assisted process writing with academic integrity guidance) and a control group (conventional instruction). Students completed a descriptive writing test and a plagiarism-awareness questionnaire. Data were analyzed using one-way MANOVA. The results revealed a significant multivariate effect, with the experimental group outperforming the control group in writing (M=73.76 vs 62.76) and plagiarism awareness (M=134.00 vs 88.85). These findings highlight ChatGPT’s potential to enhance both writing proficiency and academic integrity when integrated with explicit instruction on paraphrasing, citation, and ethical AI use.